Mobile C‐Arm with a CMOS detector: Technical assessment of fluoroscopy and Cone‐Beam CT imaging performance - Sheth, Niral M. (Med Phys, 2018)
PURPOSE: Indirect‐detection CMOS flat‐panel detectors (FPDs) offer fine pixel pitch, fast readout, and low electronic noise in comparison to current a‐Si:H FPDs. This work investigates the extent to which these potential advantages affect imaging performance in mobile C‐arm fluoroscopy and cone‐beam CT (CBCT). METHODS: FPDs based on CMOS (Xineos 3030HS, 0.151 mm pixel pitch) or a‐Si:H (PaxScan 3030X, 0.194 mm pixel pitch) sensors were outfitted on equivalent mobile C‐arms for fluoroscopy and CBCT. Technical assessment of 2D and 3D imaging performance included measurement of electronic noise, gain, lag, modulation transfer function (MTF), noise‐power spectrum (NPS), detective quantum efficiency (DQE), and noise‐equivalent quanta (NEQ) in fluoroscopy (with entrance air kerma ranging 5–800 nGy per frame) and cone‐beam CT (with weighted CT dose index, CTDI (w), ranging 0.08–1 mGy). Image quality was evaluated by clinicians in vascular, orthopaedic, and neurological surgery in realistic interventional scenarios with cadaver subjects emulating a variety of 2D and 3D imaging tasks. RESULTS: The CMOS FPD exhibited ~2–3× lower electronic noise and ~7× lower image lag than the a‐Si:H FPD. The 2D (projection) DQE was superior for CMOS at ≤50 nGy per frame, especially at high spatial frequencies (~2% improvement at 0.5 mm(−1) and ≥50% improvement at 2.3 mm(−1)) and was somewhat inferior at moderate‐high doses (up to 18% lower DQE for CMOS at 0.5 mm(−1)). For smooth CBCT reconstructions (low‐frequency imaging tasks), CMOS exhibited ~10%–20% higher NEQ (at 0.1–0.5 mm(−1)) at the lowest dose levels (CTDI (w) ≤0.1 mGy), while the a‐Si:H system yielded slightly (~5%) improved NEQ (at 0.1–0.5 lp/mm) at higher dose levels (CTDI (w) ≥0.6 mGy). For sharp CBCT reconstructions (high‐frequency imaging tasks), NEQ was ~32% higher above 1 mm(−1) for the CMOS system at mid‐high‐dose levels and ≥75% higher at the lowest dose levels (CTDI (w) ≤0.1 mGy). Observer assessment of 2D and 3D cadaver images corroborated the objective metrics with respect to a variety of pertinent interventional imaging tasks. CONCLUSION: Measurements of image noise, spatial resolution, DQE, and NEQ indicate improved low‐dose performance for the CMOS‐based system, particularly at lower doses and higher spatial frequencies. Assessment in realistic imaging scenarios confirmed improved visibility of fine details in low‐dose fluoroscopy and CBCT. The results quantitate the extent to which CMOS detectors improve mobile C‐arm imaging performance, especially in 2D and 3D imaging scenarios involving high‐resolution tasks and low‐dose conditions.